On a Subordination Associated with a Certain Subclass of Analytic Functions Defined by Salagean Derivatives - R. A. Bello; T. O. Opoola (International Journal of Mathematics And its Applications, 2017)
In this paper we discuss some subordination results for a subclass of functions analytic in the unit disk $U$.